Anti Inflammation Activity of Ginger (Zingiber officinale) Oleoresin on Kidney of Rats Under Stress Condition - Tutik Wresdiyati; Made Astawan; I Ketut Mudite Adnyane (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
The present study was conducted to observe the role of antioxidant content of ginger oleoresin (Zingiber officinale) on inflammation in the kidney of rats under stress condition, as an anti inflammation. A total of sixty male Wistar rats were used for this study. They were divided into twelve groups; (1) control group, without treatment of both stress and oleoresin, (2) stress group, was treated by stress only, without oleoresin treatment, while (3) and (4) are groups that were treated by stress and then fed by standard feed for three and seven days, without oleoresin. Group (5) to group (12) were treated by stress and then followed by treatment of oleoresin for three and seven days. The doses of oleoresin were 20, 40, 60, and 80 mg/kgBW/day. Stress condition was done by 5 days fasting and swimming for 5 minutes/day, while drinking water was provided ad libitum. The highest number of inflammatory cells in the kidney of rats was observed in the stress group. The treatment of oleoresin after fasting stress showed decreasing of the number of inflammatory cells in the tissues. The decreasing rate was higher in the higher dose of oleoresin. The treatment groups that showed the number of inflammatory cells not significantly different from that of control group are treated groups receiving oleoresin 60 mg/kgBW/day for seven days, and 80 mg/kgBW/day for three and seven days, respectively. These results showed that ginger oleoresin has anti inflammatory effect in the kidney of rats kept under stress condition. Key words : Oleoresin, ginger, inflammation, kidney, rat, stress.